Gold Micropetals Self‐Assembled by Shadow‐Sphere Lithography for Optofluidic Control. Issue 18 (7th April 2022) - Namura, Kyoko; Hanai, Shunya; Kondo, Shuji; Kumar, Samir; Suzuki, Motofumi
Abstract: The self‐assembly of gold micropetals and microfluidic control using their photothermal properties are demonstrated experimentally in this work. Gold micropetals are fabricated on a glass substrate using the shadow‐sphere lithography technique. Each micropetal consists of two areas with thin gold films of different thicknesses resulting in an inhomogeneous optical absorption distribution. The photothermal property of the micropetal results in the generation of a water vapor microbubble on the micropetal when the micropetal is immersed in degassed water and irradiated by a continuous wave laser. By applying a temperature gradient to the microbubble, Marangoni flow in the direction parallel to the substrate is successfully induced. The direction of the flow varies with the combination of the optical absorption distribution in the micropetal and the laser power. This variation can be explained by the position of the bubble on the micropetal and the resulting temperature gradient around the bubble. Controlling the position at which the bubble is generated on the micropetal is found to be important for controlling the flow direction. This technique allows microfluids to be pumped through the irradiation of light with a simple intensity distribution on spatially arranged micropetals. Abstract : Petal‐like gold microstructures with optimum optical absorption distribution are successfully self‐assembled via the shadow‐sphere lithography technique. Microbubble generation and temperature gradient control are realized by homogeneous laser beam irradiation on the gold micropetal because of its photothermal property. The temperature gradient then induces the rapid flow around the bubble and pumps fluid along the substrate surface.